Good Corporate Governance (GCG) and Financial Performance as Determinants of Credit Risk at Rural Banks (BPR) - Azahra Nur Afifah; Dewi Susilowati (The Indonesian Journal of Accounting Research, 2026)
The focus of this study is to examine the role of Good Corporate Governance (GCG) and financial performance in influencing the level of credit risk faced by rural banks (BPR). The research method applied in this study is a quantitative method using secondary data sourced from annual financial reports and governance reports of BPRs for the 2024 reporting period. The research sample consisted of 113 BPRs located in Central Java and registered with the Indonesian Rural Banks Association (PERBARINDO). Multiple linear regression models were used to analyze the data with the help of the SPSS program. The test results show that GCG and profitability have no effect on credit risk, while liquidity and operational efficiency have a positive effect on credit risk. These findings indicate that the implementation of GCG is not yet substantially effective in preventing credit risk, while profitability is not yet an effective indicator in explaining credit risk. Meanwhile, liquidity pressure and operational efficiency are factors that influence the increase in credit risk at BPRs. This study strengthens the body of literature concerning credit risk in BPRs. From a practical perspective, the findings of this study can be used as a basis for evaluation for BPR management to strengthen governance quality, for regulators to improve the effectiveness of supervision, and for customers and investors as a reference in making business decisions and assessing the condition of BPRs.